Enseignement de la langue et de la littérature françaises médiévales en Ontario (Canada anglophone) : de l’utilité d’une troisième langue… morte - Corinne Denoyelle; Mario Longtin (Perspectives Médiévales)
Teaching Old French language and literature, away from the context of teacher's examination and ranking in France, requires a certain degree of innovation. It is especially true in the English speaking South West Ontario where the student body is both diverse and multiculturally rich. In that context, Old French language and literature are often seen as strange topics to focus on, especially since the textbooks are rarely adapted to their level of French, not to mention their knowledge of the specific history of the French medieval period. This article addresses some of the problems of teaching Old French language and literature as second language acquisition tools by suggesting approaches that have proven successful in our teaching practice. A hands on approach is especially productive, as students love to work directly from digitised manuscripts. Such an initiation to medieval writings in its manuscript context stimulates students' curiosity and offers them the extra motivation to discover an otherwise very abstract topic for any learner of French language and literature outside of France.